2000
DOI: 10.4049/jimmunol.164.3.1617
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of a CpG Phosphorothioate Oligodeoxynucleotide for Activating Primate Immune Responses In Vitro and In Vivo

Abstract: Oligodeoxynucleotides (ODN) containing unmethylated CpG dinucleotides within specific sequence contexts (CpG motifs) are detected, like bacterial or viral DNA, as a danger signal by the vertebrate immune system. CpG ODN synthesized with a nuclease-resistant phosphorothioate backbone have been shown to be potent Th1-directed adjuvants in mice, but these motifs have been relatively inactive on primate leukocytes in vitro. Moreover, in vitro assays that predict in vivo adjuvant activity for primates have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
400
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 540 publications
(415 citation statements)
references
References 43 publications
(29 reference statements)
13
400
1
1
Order By: Relevance
“…In contrast, in the present study, we observed a high penetrance of arthritis in this rat strain using a similar protocol for injection of CpG/ IFA. The discrepancy of these results with the data of Ronaghy et al might be explained by the use of different oligodinucleotide sequences, since it has previously been shown that the immunostimulatory effect of CpG ODN is determined not only by the CpG motif itself, but also by the flanking nucleotide sequences (23).…”
Section: Discussionmentioning
(Expert classified)
“…In contrast, in the present study, we observed a high penetrance of arthritis in this rat strain using a similar protocol for injection of CpG/ IFA. The discrepancy of these results with the data of Ronaghy et al might be explained by the use of different oligodinucleotide sequences, since it has previously been shown that the immunostimulatory effect of CpG ODN is determined not only by the CpG motif itself, but also by the flanking nucleotide sequences (23).…”
Section: Discussionmentioning
(Expert classified)
“…CpG-activated PDC indirectly activate other immune cells such as monocytes [40,41], NK cells, c/d T cells [42] and memory a/b T cells [43,44]. CpG ODN are potent humoral vaccine adjuvants in primates [45][46][47][48][49] and in humans [50].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of murine and human B cells by CpG motif containing DNA (CpG DNA) is well established (12)(13)(14). In fact, CpG motifs were discovered based on B cell stimulation (15), and B cells were the first immune cell subset in humans identified to respond to CpG DNA in a CpG-specific fashion (16,17). CpG oligodeoxynucleotides (ODN) 3 license human CD40L-primed B cells to produce high amounts of IL-12 and to support IFN-␥ production in CD4 T cells (18).…”
mentioning
confidence: 99%